2022
DOI: 10.3389/fchem.2022.1003086
|View full text |Cite
|
Sign up to set email alerts
|

Carbon fixation of CO2 via cyclic reactions with borane in gaseous atmosphere leading to formic acid (and metaboric acid); A potential energy surface (PES) study

Abstract: Carbon dioxide (CO2), a stable gaseous species, occupies the troposphere layer of the atmosphere. Following it, the environment gets warmer, and the ecosystem changes as a consequence of disrupting the natural order of our life. Due to this, in the present reasearch, the possibility of carbon fixation of CO2 by using borane was investigated. To conduct this, each of the probable reaction channels between borane and CO2 was investigated to find the fate of this species. The results indicate that among all the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
0
0
Order By: Relevance
“…These researches were performed by different experimental as well as theoretical approaches [12][13][14][15]. Somehow, even in the production of organic molecules especially in drug synthesis, scientists made attempt to develop green, catalyst-free or ecofriendly methods [16][17][18][19][20][21][22][23]. For example, the researches showed that existence of high dosages of some heavy metal ions like mercury, or cadmium, and lead [24] in drinking water or food could lead to metabolic syndrome or even damage in organs.…”
Section: Introductionmentioning
confidence: 99%
“…These researches were performed by different experimental as well as theoretical approaches [12][13][14][15]. Somehow, even in the production of organic molecules especially in drug synthesis, scientists made attempt to develop green, catalyst-free or ecofriendly methods [16][17][18][19][20][21][22][23]. For example, the researches showed that existence of high dosages of some heavy metal ions like mercury, or cadmium, and lead [24] in drinking water or food could lead to metabolic syndrome or even damage in organs.…”
Section: Introductionmentioning
confidence: 99%